2018
DOI: 10.1210/jc.2018-02195
|View full text |Cite
|
Sign up to set email alerts
|

Water Supplementation Reduces Copeptin and Plasma Glucose in Adults With High Copeptin: The H2O Metabolism Pilot Study

Abstract: Objective Because elevated copeptin, a marker of vasopressin, is linked to low water intake and high diabetes risk, we tested the effect of water supplementation on copeptin and fasting glucose. Design, Setting, and Participants Thirty-one healthy adults with high copeptin (>10.7 pmol · L −1 in men and >6.1 pmol·L −1 in women) identified in a population-based survey from 2013 to 2015 and with a current 24-hour urine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 41 publications
(44 reference statements)
4
45
0
Order By: Relevance
“…The current study is complementary to and expands our previous finding from an experimental study in humans in which we showed that individuals with low water intake (measured as low 24 h urine volume, high 24 h u-Osm and high copeptin) express a reduction of fasting plasma glucose as a response to increased water intake [9]. In another previous study, we showed that increased water intake in individuals with low water intake was associated with a reduction of the diabetogenic hormone glucagon [20], implicating glucagon as a possible contributing factor to elevated fasting glucose among individuals with low water intake.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The current study is complementary to and expands our previous finding from an experimental study in humans in which we showed that individuals with low water intake (measured as low 24 h urine volume, high 24 h u-Osm and high copeptin) express a reduction of fasting plasma glucose as a response to increased water intake [9]. In another previous study, we showed that increased water intake in individuals with low water intake was associated with a reduction of the diabetogenic hormone glucagon [20], implicating glucagon as a possible contributing factor to elevated fasting glucose among individuals with low water intake.…”
Section: Discussionsupporting
confidence: 79%
“…Elevated plasma copeptin, a reliable marker of VP secretion, has previously been associated with multiple components of the metabolic syndrome [2][3][4] and with increased risk of diabetes development [5][6][7]. Previous experimental studies [8,9] and a Mendelian randomization study [10] points at a causal association between elevated copeptin concentration and increased metabolic risk. It can be speculated that this relationship may be explained by effects mediated by VP receptors expressed in the liver, the pancreas and in the anterior pituitary gland, which potentially could affect glucose metabolism in many different ways by inducing gluconeogenesis, glycogenolysis, glucagon secretion, and increased cortisol release [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the potential benefit of improved hydration status on glucose metabolism should be tested in future clinical trials. Actually, a recent study showed that, in adults with high copeptin levels, an increased hydration induced not only a significant decline in copeptin (as expected) but also a significant decline in glycaemia (37) . In the present study, we found that increased USG was associated with increased trunk fat and decreased leg fat, resulting in increased TLR, after adjusting for age, sex, habitual patterns, various cardiovascular risks and plain water and energy intakes.…”
Section: Discussionsupporting
confidence: 66%
“…Longitudinal data suggest parallel relationships between various correlates of osmotic stress on cells and risk of the metabolic syndrome. Behavioral determinants of hyperosmotic stress on cells, such as salt intake, lower absolute water intake, and intake of hypertonic beverages such as sugar-sweetened beverages instead of drinking water [97][98][99][100][101]; blood biomarker measures of hyperosmotic stress on cells, such as serum hypernatremia, hypertonicity, or hyperosmolality [26,32,33,38,88,102]; intracellular measures of biochemical response to hyperosmotic cell shrinkage such as upregulation of the serumand glucocorticoid-inducible kinase 1 (SGK1) [103,104]; and physiologic measures of response to hyperosmotic cell shrinkage, such as increases in plasma copeptin [18,19,[105][106][107][108], are independently associated with incident metabolic dysregulation and/or chronic disease risk.…”
Section: Potential Causal Mechanisms Linking Hydration With Metabolicmentioning
confidence: 99%